2014
DOI: 10.1136/bmjquality.u205646.w2316
|View full text |Cite
|
Sign up to set email alerts
|

Recovery coaching in an acute older people rehabiliation ward

Abstract: Our patient, carer, and staff feedback clearly tells us that elderly patients are frequently disempowered by acute care provision, environments, and attitudes. This debilitates individuals mentally and physically, reducing their independent functioning, and may mean that they require prolonged care or are unfit to return home.We developed the concept of “recovery coaching” to support acute inpatient elderly care rehabilitation. We designed a training intervention to achieve “coaching conversations” between our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Interventions aiming to improve patient-centered care often focus on external participation or rather patient-professional interaction, e.g. shared decision-making [ 3 , 8 ] or health coaching [ 19 , 20 ]. However, it could also be shown that team interventions in health care have a positive impact on interprofessional teamwork [ 1 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interventions aiming to improve patient-centered care often focus on external participation or rather patient-professional interaction, e.g. shared decision-making [ 3 , 8 ] or health coaching [ 19 , 20 ]. However, it could also be shown that team interventions in health care have a positive impact on interprofessional teamwork [ 1 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis presented here demonstrates that a coaching approach can be highly successful in getting staff to think again about their interactions with patients and to focus on strategies that foster and establish independence, rather than on strategies that solve immediate problems. The usefulness of this approach is further supported by the analysis of our patient-data, which shows (for example) a significant reduction in additional care needs on discharge in patient groups who received the intervention, when compared with those who did not (see Kibble et al, 2014).…”
Section: Discussionmentioning
confidence: 74%
“…This coaching intervention was evaluated using a before-and-after design, where data were collected to assess the impact of recovery coaching on patients’ independent functioning and recovery, service improvements, and the staff. The quantitative data and full methodology of this evaluation have been reported elsewhere (Kibble et al, 2014).…”
Section: Methodsmentioning
confidence: 99%